A new concrete-glulam prefabricated composite wall system: Thermal behavior, life cycle assessment and structural response. (September 2018) - Boscato, G.; Mora, T. Dalla; Peron, F.; Russo, S.; Romagnoni, P.
Abstract: This study analyses a new hybrid construction system, the CGFP - Concrete Glulam Framed Panel - that merges the two mostly used materials in frame technology. It is a prefabricated composite wall made of a reinforced concrete slab and a glulam frame. The strength and stiffness of CGFP have been investigated by load-displacements tests and thermal performance was evaluated by means of a hot-box apparatus. Moreover, the environmental impacts of the system are verified defining its Carbon Footprint and Embodied Energy. The efficacy of the proposed system was validated by experimental and numerical analysis. Mechanical and thermal properties have been evaluated by means of experimental and numerical tests whose results have been compared showing a good agreement. By structural point of view, the strength and the deformation capacity are ensured through the consecutive and interactive structural response between the wood frame and the concrete slab. By the thermal and environmental point of view, thermal resistance obtained with different kind of insulation materials have been analysed and a calculation of the amount of the Carbon Footprint and Embodied Energy was already performed. The CGFP panel shows a good thermal performance, a low environmental impact respect to similar construction systems and promising structural behavior. Highlights: The paper resumes and completes results of a three years investigation on the structural, thermal and environmental performances of a concrete-glulam prefabricated composite wall system. The strength and stiffness of concrete-glulam prefabricated panels have been investigated by load-displacements tests; thermal performance was analysed matching values given by numerical simulations and experimental tests executed by hot box apparatus. The environmental impacts of the system is verified defining its Carbon Footprint and Embodied Energy by using the life cycle assessment method.